Effects of high-intensity functional training on physical fitness and sport-specific performance among the athletes: A systematic review with meta-analysis - Wang, X.; Soh, K. G.; Samsudin, S.; Deng, N.; Liu, X.; Zhao, Y.; Akbar, S. (PLOS ONE, 2023)
Objective This study aims to meta-analyze the impact of high-intensity functional training on athletes` physical fitness and sport-specific performance.